Effects of Acid Treatments on Surface Property and Mercury Removal Performance of Lignite Semi-coke - Zhang, Huawei; Liu, Xiuli; Wang, Li; Liang, Peng (Asian Journal of Chemistry, 2014)
In this study, hydrochloric acid, nitric acid and sulfuric acid are, respectively applied to lignite semi-coke from Inner Mongolia for surface modification processing and the effects of various acid treatments on the lignite semi-coke surface property and mercury removal performance are observed. The results show that the acid treatments have significant effects on the specific surface area, aperture structure, surface chemical functional group and other physical and chemical properties. In addition, the micropore ratio and pore volume of semi-coke are the major factors determining the mercury removal efficiency at low temperature; the surface oxygen-containing functional groups (carboxyl, lactone, phenolic hydroxy, etc.), the positively charged nitrogenous functional groups and the other heteroatom functional groups are the active sites of gaseous Hg0 catalytic oxidation reactions and determine the mercury removal efficiency of semi-coke at high temperature. It is shown that the cellular structure of the nitric acid modified semi-coke is the most highly developed and has a strong mercury removal performance at 30 °C. The hydrochloric acid treatment leaves a Cl-C-Cl functional group which may easily react with gaseous Hg0 on the surface of semi-coke, causes the carboxyl and phenolic hydroxy contents to increase and greatly improves the mercury removing efficiency of lignite semi-coke at 140 °C.